PEMANFAATAN TEKNOLOGI UNMANNED AERIAL VEHICLE (UAV) QUADCOPTER SEBAGAI PEMETIK BUAH DURIAN - Laksha, Ali Dwi; Feriyanto, Dwi; Ariyanti, Septika; andika, tahta herdian (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2024)
Farmers certainly want a short and adequate time to collect their crops when the harvest season arrives. Such as durian farmers, most of them still use manual methods to harvest their agricultural products, even though there are already tools that can help make it easier when climbing trees. However, they still have risks because farmers still have to climb trees with tall tree branches, not to mention when the weather is not friendly and the trees are slippery due to rain. Of course, it is very risky to harvest agricultural products. The unmanned aerial vehicle will cut the stalks on the durian fruit with a circular blade-cutting mechanism. The blades are connected via a gear designed as a cutter capable of reaching the durian fruit stalk. The other motor that drives the cutting knife has been modified via the central controller to connect to the remote control so that the auxiliary motor on the cutting knife does not require a manual switch to turn it on. Using Quadcopter Unmanned Aerial Vehicle (UAV) Technology as a Durian Fruit Picker is a solution for durian farmers who have plantations with high tree branches. Drones can reach fruit at the tree's end with the added cutter module mechanism. This drone has effectiveness in terms of time which is better than picking durian fruit manually. The design of this cutter can be adjusted at speed to adjust the drone's flight stability.